2019
DOI: 10.3389/fneur.2019.00592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperhomocysteinemia on Clinical Outcome and Hemorrhagic Transformation After Thrombolysis in Ischemic Stroke Patients

Abstract: Background and Purpose: Hyperhomocysteinemia (Hhcy) is a well-known risk factor for ischemic stroke. However, the role of Hhcy in the clinical outcome of ischemic stroke has not been fully elucidated. In addition, previous studies have found that Hhcy was implicated in the disruption of the blood-brain barrier, which may increase the risk of hemorrhagic transformation (HT) after thrombolysis. Thus, the aim of this study was to investigate the effect of Hhcy on the clinical outcome and HT after throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…To further confirm the association between Hcy levels and clinical outcome of AIS patients treated with thrombolytic therapy, we conducted this retrospective study. Consistent with the previous retrospective studies conducted by Ling et al (2018) , Luo et al (2019) and Yao et al (2016) , we found that there exists a correlation between Hcy levels and poor prognosis after acute thrombolytic therapy in AIS patients in this retrospective study. And we indicated that higher Hcy levels have a negative impact on prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To further confirm the association between Hcy levels and clinical outcome of AIS patients treated with thrombolytic therapy, we conducted this retrospective study. Consistent with the previous retrospective studies conducted by Ling et al (2018) , Luo et al (2019) and Yao et al (2016) , we found that there exists a correlation between Hcy levels and poor prognosis after acute thrombolytic therapy in AIS patients in this retrospective study. And we indicated that higher Hcy levels have a negative impact on prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Though a small number of studies have already been published, the prognostic value of Hcy levels in patients with AIS after IVT remains controversial. Some investigations revealed that Hhcy was correlated with unfavorable outcomes in patients with ischemic stroke ( Ling et al, 2018 ; Luo et al, 2019 ; Yao et al, 2016 ), whereas some other studies indicated that there was no significant correlation between Hhcy and ischemic stroke patients’ clinical outcome ( Ribo et al, 2004a , 2004b ). To further confirm the association between Hcy levels and clinical outcome of AIS patients treated with thrombolytic therapy, we conducted this retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes was defined as FBG levels ≥ 7.0 mmol/L or any self-declared history of diabetes or current drug use for diabetes [ 20 ]. Dyslipidemia was defined as those taking oral anti-dyslipidemic drugs, having any self-declared history, or at any one of the following outcomes: TG levels ≥ 1.70 mmol/L, TC levels ≥ 5.18 mmol/L, LDL-C levels ≥ 3.37 mmol/L, or HDL-C level ≤ 1.04 mmol/L [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…45 A higher level of homocysteine was reported to be associated with an increased risk of poor outcome after thrombolysis in AIS patients. [46][47][48] Although found to be independent predictors after multivariable logistic analysis, hypertension and Hhcy are only a small proportion of our model. The AUC value of the N2H3 nomogram was 0.872 (95% CI, 0.841-0.902), which is higher than the value of the START nomogram (AUC, 0.766; 95% CI, 0.707-0.826).…”
Section: Discussionmentioning
confidence: 99%
“…45 A higher level of homocysteine was reported to be associated with an increased risk of poor outcome after thrombolysis in AIS patients. [46][47][48] Although found to be independent predictors after multivariable logistic analysis, hypertension and Hhcy are only a small proportion of our model.…”
Section: Discussionmentioning
confidence: 99%